Customer Satisfaction toward Digital Banking Services among Young Adults - Gan Kia Hui; Hani Ariesha Binti Khursani; Goh Jie Yi; Gooi Yi Heng; Ge Ru Xi; Daisy Mui Hung Kee (AIBPM Publisher, 2026)
This study aims to investigate customer satisfaction toward digital banking services among young adults. As digital banking becomes an essential part of financial activities, understanding factors that influence user satisfaction is crucial. Four dimensions of reliability, security, responsiveness, and convenience are the areas of focus of this study to understand their effects on overall satisfaction. A quantitative research design is utilized by conducting an online survey to 150 young consumers aged between 18 and 30. The postulated results indicate that security and reliability have the highest positive influence on customer satisfaction, followed by responsiveness and convenience having considerable influence. It is expected that the findings of the study will provide pragmatic suggestions to banks and fintech companies to improve service quality, customer credibility, as well as long-term relationship with young adult consumers.